The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ic9020993
|View full text |Cite
|
Sign up to set email alerts
|

Heme−Copper−Dioxygen Complexes: Toward Understanding Ligand-Environmental Effects on the Coordination Geometry, Electronic Structure, and Reactivity

Abstract: The nature of the ligand is an important aspect of controlling structure and reactivity in coordination chemistry. In connection with our study of heme/copper/oxygen reactivity relevant to cytochrome c oxidase O 2 -reduction chemistry, we compare the molecular and electronic structure of two highspin heme-peroxo-copper [Fe III -O 2 2--Cu II ] + complexes containing N 4 -tetradentate (1) or N 3 -tridentate (2) copper ligands. Combining previously reported and new resonance Raman and EXAFS data coupled to DFT ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(117 citation statements)
references
References 89 publications
4
108
0
Order By: Relevance
“…Further study of complexes 40 and 42 by DFT calculations showed this decrease in ν(O-O) to be the result of efficient backbonding from the copper center into the σ* orbital of the peroxo ligand in the case of the η 2 :η 2 binding configuration. Given the conformational restraints of the copper supporting ligand for compound 40, such backbonding does not occur [130]. Axial ligation at the heme center has also been demonstrated to have an effect on the binding mode of the peroxo bridge.…”
Section: (μ-Peroxo)iron-copper Intermediatesmentioning
confidence: 99%
“…Further study of complexes 40 and 42 by DFT calculations showed this decrease in ν(O-O) to be the result of efficient backbonding from the copper center into the σ* orbital of the peroxo ligand in the case of the η 2 :η 2 binding configuration. Given the conformational restraints of the copper supporting ligand for compound 40, such backbonding does not occur [130]. Axial ligation at the heme center has also been demonstrated to have an effect on the binding mode of the peroxo bridge.…”
Section: (μ-Peroxo)iron-copper Intermediatesmentioning
confidence: 99%
“…-OH À and a phenol radical ( Figure 12) [44]. Thus, in order to reduce the bound peroxide in the compounds given in Figure 12, the tridentate Cu complex stabilizes Figure 12 Formation of a phenoxy radical by addition of a phenol derivative to the heme-peroxy-tridentate copper complex (2b).…”
Section: Biomimetic Studiesmentioning
confidence: 99%
“…Thus, in order to reduce the bound peroxide in the compounds given in Figure 12, the tridentate Cu complex stabilizes Figure 12 Formation of a phenoxy radical by addition of a phenol derivative to the heme-peroxy-tridentate copper complex (2b). Reproduced by permission from [44]; copyright 2010 American Chemical Society. the low-spin state which has reactivity towards the phenolic OH group.…”
Section: Biomimetic Studiesmentioning
confidence: 99%
See 2 more Smart Citations